El diagnostico de la exocortis utilizando estacas de cidra enraizadas - Perez, J.M.=700 1 Gonzalez, M.
(Es, En)
Ilus., 7 ref.
Keywords: CITRUS MEDICA; VIRUS; ANALISIS DE TEJIDOS; HOJAS; SINTOMAS; INOCULACION; INJERTO; CORTEZA; VIROSIS; ENRAIZAMIENTO; TIERRA; CUBA; CIENCIA Y TECNICA EN LA AGRICULTURA: CITRICOS Y OTROS FRUTALES